Fatores associados à qualidade de vida de estudantes de Medicina do Centro Universitário de Caratinga (UNEC)-MG - SILVA, R. C. (2019)
Introduction: The quality of life of medical students has long been the object of attention and research, since, due to the stress inherent to the course, this population is vulnerable to mental disorders affecting their quality of life. Knowing about the medical students’ quality of life and general mental health, as well as the related factors, is critical to support actions improving the medical students’ learning process. Objective: Evaluating the medical students’ Quality of Life (and related factors) at the University Center of Caratinga (UNEC). Methodology: This descriptive, cross-sectional and quantitative study was conducted through a self-administered questionnaire containing questions on sociodemographic data, quality of life (WHOQOL) and general mental health (Goldberg’s QSG). The population consisted of medical students at UNEC-Caratinga, Minas Gerais, Brazil. A total of 94 medical students were divided into three groups, namely, G1 (1st year), with 32 students, G2 (3rd year), with 30 students, and G3 (5th year), with 32 students, who were analyzed through descriptive analysis, with the use of tools such as Chi-square test, Pearson’s correlation, Student’s t-test and/or Analysis of Variance (ANOVA). Cluster analysis was performed at the statistical significance of a 5% probability. Results: The sociodemographic data showed that 58.5% of the students were female, with ages varying between 19 and 24 years old, 80.8% of them were single and 61.7% from the urban area of Caratinga, where the University Center is located. There was no significant difference in the students’ mean scores under the domains of the quality of life and general mental health questionnaires, over the different course levels. According to the descriptive analysis of the domains evaluated, the students presented moderate quality of life, with scores over 60, and the variable “marital status” influenced the social relations domain (0.043 p> 0.05), wherein single students scored higher than non-single ones. Three groups with different quality of life profiles were identified, classified according to a lower (25.5%), intermediate (30.9%), and higher (43.6%) perception of QoL. A significant correlation was observed between general mental health (QSG) and quality of life factors, wherein a worse state of general mental health is associated with a lower quality of life. The incidence of minor mental disorder detected in the sample under analysis was of 41.5% among the students, of which the highest-scoring disorder was psychic stress (64.1%), and the lowest one death wish (39.8%). Conclusion: The medical students under analysis have a good perception of their quality of life. The course level (years of study) had no significant influence, and single students presented a significantly better result with respect to their perception of their quality of life. The incidence of minor mental disorders in the population under study was high, with a prevalence of psychic stress.